Oral Hygiene Programs/Techniques used in Patients with Esophagectomy in the Acute Phase: Protocol for a Scoping Review - Flynn, Eadaoin; Regan, Julie (My University, 2025)
Background: Maintaining or improving oral hygiene is crucial for paGents who have undergone esophagectomy due to esophageal cancer. Research shows that good oral hygiene is associated with fewer complicaGons and shorter hospital stays aIer surgery. While there are many studies highlighGng the importance of oral care in the preoperaGve phase, techniques and protocols for oral hygiene care in the postoperaGve phase remain unclear. The need for comprehensive guidance for healthcare professionals is urgent. Objec0ves: The aim of the study is to idenGfy the techniques and protocols used to maintain or improve oral hygiene in paGents aIer esophagectomy and to describe the general benefits of these strategies. To achieve these goals, a scoping review will be conducted to gather all available informaGon from exisGng studies. Methods: The review will include the use of five electronic databases to search for literature. The search will be conducted using three main terms: ’’oral hygiene”, ‘’esophageal cancer’’ and ”esophagectomy”. Studies that meet the inclusion criteria will be assessed by two reviewers for selecGon, and their data will be extracted using specific tools (e.g. Covidence and EndNote). Conclusions: The review will provide a comprehensive account of the techniques and protocols used for maintaining oral hygiene in paGents who have undergone esophagectomy. The results of this review will provide valuable informaGon for clinical pracGce and help healthcare professionals, especially Speech and Language Therapists, in beXer managing these paGents. AddiGonally, this review will serve as a foundaGon for future research on the topic.
PRODUCED
Department of Clinical Speech and Language Studies, Trinity College Dublin.
Keywords: Ageing; DYSPHAGIA; Dysphagia in cancer and palliative care; Other; Health